Chemical Bingo: A playful approach to teaching the Periodic Table - Gomes, Caique Douglas Pantoja; Negão, Charles Alberto Brito; Camarão, Matheus Ramon Blanco; Amorim, Leonardo Moraes; Pinheiro , Heloiza Verena Alves; de Abreu, Alfredo Gabryel Bastos; Sanches, Andressa de Paula Amaral; Neto, Lázaro de Lima Pantoja; de Souza, Ewerton Carvalho; Silva, Antonio dos Santos (Seven Editora, 2024)
Educational games currently play a very important role in education, offering an innovative approach to learning, facilitating the retention of knowledge. In view of this, it was sought, through the present work, to evaluate the acceptability of the use of games for the teaching of chemistry in the undergraduate course (pharmacy course), more specifically, the teaching of the periodic table. For the analysis, a bingo-type game was used, which was applied and then evaluated through a questionnaire. As a result, an average score attributed to the game of 9.7 was obtained, and positive answers to the other questions were 100%. Thus, good perspectives of this methodology are proven by the students and its effectiveness and efficiency in pedagogical practice. DOI:https://doi.org/10.56238/sevened2024.015-009